Non-essential heavy metal effects in cardiovascular diseases: an overview of systematic reviews - Nucera, Saverio; Serra, Maria; Caminiti, Rosamaria; Ruga, Stefano; Passacatini, Lucia Carmela; Macrì, Roberta; Scarano, Federica; Maiuolo, Jessica; Bulotta, Rosamaria; Mollace, Rocco; Bosco, Francesca; Guarnieri, Lorenza; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Cardiovascular diseases (CVDs) are the most important cause of premature death and disability worldwide. Environmental degradation and cardiovascular diseases are two keys to health challenges, characterized by a constant evolution in an industrialized world that exploits natural resources regardless of the consequences for health. The etiological risk factors of CVDs are widely known and include dyslipidemia, obesity, diabetes, and chronic cigarette consumption. However, one component that is often underestimated is exposure to heavy metals. The biological perspective explains that different metals play different roles. They are therefore classified into essential heavy metals, which are present in organisms where they perform important vital functions, especially in various physiological processes, or non-essential heavy metals, with a no biological role but, nonetheless, remain in the environment in which they are absorbed. Although both types of metal ions are many times chemically similar and can bind to the same biological ligands, the attention given today to nonessential metals in several eukaryotic species is starting to raise strong concerns due to an exponential increase in their concentrations. The aim of this systematic review was to assess possible correlations between exposure to nonessential heavy metals and increased incidence of cardiovascular disease, reporting the results of studies published in the last 5 years through March 2023. Methods The studies includes reviews retrieved from PubMed, Medline, Embase, and Web of Science databases, in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement and following the PICO (Population Intervention Comparison Outcome Population) framework. Results Eight reviews, including a total of 153 studies, were identified. Seven of these review enlighted the association between CVDs and non-essential heavy metals chronic exposure. Discussion It is evident that exposure to heavy metals represent a risk factor for CVDs onset. However, further studies are needed to better understand the effects caused by these metals.